A Flexible Nanocrystal Photovoltaic Ultraviolet Photodetector on a Plant Membrane. Issue 11 (23rd June 2015) - Wu, Jingda; Lin, Lih Y.
Abstract : A flexible UV photodetector is created with a reed membrane as the interspacing layer embedded with ZnO nanocrystals. The membrane's porous nature facilitates the adhesion of active materials and light scattering, and improves device performance. A sandwich structure with a vertical Schottky junction is applied to increase the device's response speed, achieving a sub‐second response time, as well as a maximum external quantum efficiency of over 3%. The device also shows a slight performance increase under bending.